4,4-Dichloro-1,3-dithietane-2-one - Tracy R. Thompson; William W. Brennessel; Erik S. Goebel; Matthew J. Turcotte; George Barany (Molbank)
The title compound, 4,4-dichloro-1,3-dithietane-2-one, was encountered when opening a commercial capped amber bottle labeled “thiophosgene” that had been stored in a cold room (4 °C) for decades without any special precautions. Treating it as an unknown, the structure was established by single crystal X-ray analysis, and confirmed by 13C NMR, FTIR, melting behavior, and elemental analysis; its behavior under several mass spectrometric conditions was also examined. The dithietane appears to be a spontaneously formed cyclodimer of thiophosgene in which exactly one (not zero, not both) of the dichloromethylene moieties has been hydrolyzed to a carbonyl function. The relative long-term stability of the hydrolyzed dimer, along with a pathway back to thiophosgene, suggests that it might serve as a storage vehicle for toxic thiophosgene. Furthermore, as noted elsewhere, the title compound reacts with nucleophiles under mild aqueous conditions, suggesting that it may be a useful probe in chemical biology.